2023
DOI: 10.1186/s12967-023-04167-7
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K-Akt-mTOR pathway mediates renal pericyte-myofibroblast transition by enhancing glycolysis through HKII

Abstract: Background Pericyte-myofibroblast transition (PMT) has been confirmed to contribute to renal fibrosis in several kidney diseases, and transforming growth factor-β1 (TGF-β1) is a well-known cytokine that drives PMT. However, the underlying mechanism has not been fully established, and little is known about the associated metabolic changes. Methods Bioinformatics analysis was used to identify transcriptomic changes during PMT. PDGFRβ + pericytes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…According to Chen et al, the pericyte-to-myofibroblast (PTM) transition mediated by TGF-β1 is characterized by increased glycolysis and elevated phosphorylation levels of serin threonine kinase mTOR. The inhibition of the PI3K-Akt-mTOR pathway resulted in decreased glycolysis, suggesting that this pathway plays a role in the regulation of PTM [67]. These results are consistent with studies in AKI animal models obtained by IRI.…”
Section: Ischemia-reperfusion Injury and Pericytessupporting
confidence: 89%
“…According to Chen et al, the pericyte-to-myofibroblast (PTM) transition mediated by TGF-β1 is characterized by increased glycolysis and elevated phosphorylation levels of serin threonine kinase mTOR. The inhibition of the PI3K-Akt-mTOR pathway resulted in decreased glycolysis, suggesting that this pathway plays a role in the regulation of PTM [67]. These results are consistent with studies in AKI animal models obtained by IRI.…”
Section: Ischemia-reperfusion Injury and Pericytessupporting
confidence: 89%
“…In addition to the Smad2/3 pathway, it seems that there also exist other inhibitory mechanisms driven by AMPK signaling. For instance, there is clear evidence indicating that TGF-β treatment can trigger myofibroblast differentiation via the PI3K/AKT/mTOR signaling pathway (Tang et al 2023 ; Chen et al 2023 ). For instance, Chen et al ( 2023 ) demonstrated that exposure to TGF-β induced the conversion of mouse renal pericytes into myofibroblasts.…”
Section: Ampk Signaling Inhibits the Differentiation Of Myofibroblastsmentioning
confidence: 99%
“…For instance, there is clear evidence indicating that TGF-β treatment can trigger myofibroblast differentiation via the PI3K/AKT/mTOR signaling pathway (Tang et al 2023 ; Chen et al 2023 ). For instance, Chen et al ( 2023 ) demonstrated that exposure to TGF-β induced the conversion of mouse renal pericytes into myofibroblasts. The TGF-β treatment of pericytes robustly increased the expression of hexokinase II which enhanced the amount of glycolysis in converted myofibroblasts.…”
Section: Ampk Signaling Inhibits the Differentiation Of Myofibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the sufficient oxygen condition, pyruvate is oxidized by pyruvate dehydrogenase to produce acetyl coenzyme A, which enters the tricarboxylic acid (TCA) cycle and OXPHOS; whereas when oxygen is absen, pyruvate is catalyzed by lactate dehydrogenase to produce lactate [ 29 ]. Increasingly, it has been shown that in addition to the significant effects of changes in kinase activity on glycolytic activity and cell growth [ 30 ], signaling pathways such as PI3K/AKT/mTOR also play an important role in cell survival and development by mediating glycolysis-related processes [ 31 ]. An increasing number of studies have shown that changes in CD8 + T cells’ glycolysis and OXPHOS have different regulatory effects on CD8 + T cell activation, differentiation, and function.…”
Section: Introductionmentioning
confidence: 99%